Distally-based Peroneus Brevis Turnover Muscle Flap in the Reconstruction of Soft Tissue Defects. Issue 12 (December 2020) - Malahias, Marco; Khalil, Haitham; Abdalbary, Sahar Ahmed; Abdelkader, Rasha
Abstract : Background: Reconstruction of the distal 3rd of the lower leg requires either local or free flap coverage if tendons or bones are exposed. The distally based, pedicled peroneus brevis (PB) flap has been shown to be a valid option in the management of distal 3rd lower limb injuries. Herein, we present 21 cases treated with distally-based PB muscle flaps between May 2017 and September 2019. The defect location varied, and included defects over the lateral and medial malleolar areas, distal tibia (middle and distal 3rd junction, and the distal 3rd), and Achilles tendon area. Methods: The PB was dissected from the lateral fibula and intermuscular septa in a cephalic to caudal direction, to a point no lower than 7 cm proximal to the lateral malleolus tip. This preserved most distal vascular perforators to the muscle, and afforded sufficient mobilization to allow successful turn-over of the muscle, with transposition into the defect within 30 minutes of tourniquet time. A meshed skin graft completed the intervention. Results: The metalwork was removed in all chronic cases (10/21), as bone union had occurred. All flaps survived completely. One patient partially lost the skin graft; the wound was healed by secondary intention. No major complications occurred and no significant patient discomfort was noted. All wounds healed completely by 9 weeks of follow-up. Conclusion: The PB turnover muscle flap is a versatile flap, ideally suited to manage up to moderately sized defects of the distal 3rd of the lower leg, with negligible postoperative morbidity.